Unveiling the therapeutic benefits of black chokeberry (Aronia melanocarpa) in alleviating hyperuricemia in mice - Liu, Chin-Yuan; Liu, Wen-Yu; Shi, Yeu-Ching; Wu, She-Ching (Frontiers in Nutrition, 2025)
BackgroundHyperuricemia not only increases the risk of cardiovascular diseases such as dyslipidemia, hypertension, coronary artery disease, obesity, metabolic syndrome, and type-2 diabetes, but also severely impacts kidney function, potentially leading to acute kidney injury and chronic kidney disease.MethodsThis study aims to investigate the health benefits of black chokeberry (Aronia melanocarpa) on hyperuricemic mice induced by oxonic acid.ResultThe experimental results showed that black chokeberry had no significant toxic or negative effects in mice. The measurement of uric acid (UA) indicated that black chokeberry suppressed the UA levels. Additionally, the xanthine oxidase activity in the high-dose group was significantly decreased, along with reductions in serum urea nitrogen and creatinine levels. Black chokeberry effectively increased the glutathione levels in hyperuricemic mice and reduced malondialdehyde levels, as well as significantly inhibiting adenosine deaminase activity.ConclusionIts efficacy is comparable to that of the marketed drug allopurinol, underscoring the potential of black chokeberry as a functional product for uric acid reduction.